Research Embedded Health Librarianship: The Canadian Landscape - Liz Dennett; Trish Chatterley; Devon Greyson; Soleil Surette (Journal of the Canadian Health Libraries Association, 2014)
Introduction: Previous research has identified various types of embedded librarianship – the clinical informationist, the academic liaison librarian, and the special librarian within a corporation. There is far less mention of librarians who are embedded in health research teams; however, the authors’ personal experiences indicate these positions are not rare. The research-embedded health librarian (REHL) provides tailored, intensive information services to a health research team in which the REHL is integrated. This research study aims to describe the REHL workforce in Canada, noting how the characteristics of both the positions and the individuals holding them differ from those of health librarians in more traditional librarian roles. Methods: As Part I of a two-part mixed methods study, an electronic survey was distributed to Canadian health librarians. The survey gathered demographic data on all respondents and information on the work environments and experiences of self-identified REHL respondents. Descriptive data analysis was conducted, and statistical differences between REHLs and non-REHLs were calculated. Results: One hundred and ninety-one individuals completed the survey, with 39 (20%) self-identifying as REHLs. The results indicated that REHLs tend to be both younger and newer to the profession than librarians in non-REHL positions. They are more likely to work for research institutes and nonprofit organizations, and they are less likely to work in hospital environments. They are also more likely to be hired on term-specific contracts than on a permanent basis. Discussion: More survey respondents identified themselves as REHLs than was anticipated, which may indicate that this a growing segment of the health librarian workforce. The high number of contract positions could be one explanation for why REHLs tend to be younger librarians or librarians who are newer to the profession, as they are just starting out in their careers. The predominance of contract positions is likely influenced by the high number of jobs in research institutes or nonprofit organizations where continuance of the positions is dependent on securing grant funding.